ChemInform Abstract: FeCl3‐Silica: A Green Approach for the Synthesis of Nitriles from Oximes. Issue 39 (September 2016) - Ghosh, Pranab; Pariyar, Gyan Chandra; Saha, Bittu; Subba, Raju
Abstract: A solvent‐free and environmentally benign protocol for the single‐step formation of nitriles (II) from aldoximes (I) using FeCl3 ‐silica medium is given.